The Toolbox for Fiber Flax Breeding: A Pipeline From Gene Expression to Fiber Quality - Galinousky, Dmitry; Mokshina, Natalia; Padvitski, Tsimafei; Ageeva, Marina; Bogdan, Victor; Kilchevsky, Alexander; Gorshkova, Tatyana (Frontiers in Genetics, 2020)
The goal of any plant breeding program is to improve quality of a target crop. Crop quality is a comprehensive feature largely determined by biological background. To improve the quality parameters of crops grown for the production of fiber, a functional approach was used to search for genes suitable for the effective manipulation of technical fiber quality. A key step was to identify genes with tissue and stage-specific pattern of expression in the developing fibers. In the current study, we investigated the relationship between gene expression evaluated in bast fibers of developing flax plants and the quality parameters of technical fibers measured after plant harvesting. Based on previously published transcriptomic data, two sets of genes that are upregulated in fibers during intrusive growth and tertiary cell wall deposition were selected. The expression level of the selected genes and fiber quality parameters were measured in fiber flax, linseed (oil flax) cultivars, and wild species that differ in type of yield and fiber quality parameters. Based on gene expression data, linear regression models for technical stem length, fiber tensile strength, and fiber flexibility were constructed, resulting in the identification of genes that have high potential for manipulating fiber quality. Chromosomal localization and single nucleotide polymorphism distribution in the selected genes were characterized for the efficacy of their use in conventional breeding and genome editing programs. Transcriptome-based selection is a highly targeted functional approach that could be used during the development of new cultivars of various crops.